"Hunting Is Our Heritage; We Commit No Offence": Kainji National Park Wildlife Poachers, Kaiama, Kwara State Nigeria. Issue 12 (1st December 2020) - Paul Mmahi, Okoro; Usman, Abubakar
ABSTRACT: So far, studies on wildlife poaching in Nigeria have focused on its health implications, motivations, and rationalizations. The methods of operation employed by the poachers to thwart enforcement of anti-poaching laws have not been examined. It is in an attempt to bridge this gap that this study examined wildlife poaching at the Kainji National Park (KNP) Kwara State, from the poachers' perspective and the various attendant schemes employed by the poachers to evade arrest and prosecution. This study interrogated how enforcement of laws against criminalized acts could be frustrated through adoption of schemes to evade arrest and prosecution, if a cultural group defines such criminalization as an incursion on their cultural heritage. It also examined forces propelling wildlife poaching at the Park. The study is of the firm believe that knowledge of these schemes would be useful to park rangers in adopting a more effective approach to tackle the crime. Knowledge of the cultural forces propelling poaching would also be useful to the government in initiating appropriate approaches to address them. The exploratory research design was employed for the study while the qualitative method was used to collect primary data. Narratives were generated through in-depth interviews with wildlife poachers at Kaiama community. Findings from the study showed that community rationalization and justification of hunting as their heritage, and perception of establishment of KNP as an incursion on their heritage was a major force propelling illegal hunting while the consequent tactics adopted by the poachers to evade arrest were: use of mystical powers, decimation of vultures, bribery, use of community residents as informants, prediction of park rangers' movements, sale of hunted animals to only familiar customers and new customers introduced by old customers, and utilization of their mastery of the forest environment. Poachers remain persistent in the act due to availability of a variety of animals to poach, and corruption among the park rangers.